Functional Properties of Muffin As Affected by Substituing Wheat Flour with Carob Powder - Červenka, Libor; Frühbauerová, Michaela; Velichová, Helena (HACCP Consulting, 2019)
Carob (Cerationa soliqua L.) pod is the good source of dietary fiber, minerals and polyphenolic substances. The aim of this study was to prepare muffin where wheat flour was substituted with carob powder, and determine some physicochemical properties. Carob powder was prepared by milling dry carob pods to particles smaller than 600 μm. Then wheat flour in muffin dough was replaced by carob powder in 5, 10, 15, and 20% (w/w) and subsequently baked at 180 °C for 20 min. It was found that the height of the muffin fortified with carob powder decreased in comaprsion with that in control muffin sample. Although the height of muffins decreased with the increase in level of carob powder, the differences were not statistically significant. Weight loss was similar for all the muffin samples in this study. Moisture content of muffins with carob powder was significantly higher than that in control. Addition of carob powder had also effect on water acitivity of muffin. While 0.905 aw was observed in control sample, significantly higher aw values were determinated in fortified muffins (0.912 – 0.923 aw). The antioxidant characteristics were determinated using spectrophotometric assays for total phenolics (TPC), total flavonoids (TFC), radical scavenging activities (DPPH, ABTS) and hydrogen peroxide scavenging (HPS). TPC values gradually increased with the increase in level of carob powder from 348.1 to 829.1 μg gallic acid.g-1 dm but TFC values significantly increased in muffin with 15 and 20% (w/w) of carob powder. All the antioxidant assays showed strong and positive association with the increase in level of carob powder. Addition of carob powder resulted in the increase of browning index and FAST index as a metrics of the formation of Maillard products.
Vliv substituce karobového prášku za pšeničnou mouku na funkční vlastnosti mufinů
Keywords: Fortification; phenolics; antioxidant; browning; Obohacení; fenolické látky; antioxidant; hnědnutí